Muon spin relaxation investigation of magnetic ordering in the hybrid organic-inorganic perovskites [(CH3)(2)NH2]M(HCOO)(3) (M=Ni, Co, Mn, Cu) - Baker, P; Lancaster, T; Franke, I; Hayes, W; Blundell, S; Pratt, F; Jain, P; Wang, Z; Kurmoo, M (2010)
Muon spin relaxation measurements are reported on samples of dimethylammonium metal formates containing magnetic divalent nickel, cobalt, manganese, and copper ions. These hybrid organic-inorganic perovskites exhibit weak ferromagnetism and are, apart from the copper system, multiferroics with well-separated magnetic and antiferroelectric transitions. We use muons to follow the sublattice magnetization, observing the effect of the spin reorientation transitions below TN and the criticality approaching TN. The multiferroic samples have three-dimensional antiferromagnetic interactions but the copper sample shows quasi-one-dimensional behavior due to its Jahn-Teller distorted structure with a ratio of its interchain and intrachain exchange constants | J′ /J | ≃0.037. © 2010 The American Physical Society.